Meningkatkan Kemampuan Penulisan Surat Dinas: Pelatihan Tata Surat dan Korespondensi untuk Tenaga Kependidikan Yayasan Lazaris, Surabaya - Yohanes Adven Sarbani; Anastasia Nelladia Cendra; Eric Sulindra; Tuti Hartani; Andreas Emmanuel Hadisoebroto; Indriana Lestari (ISAS (Indonesian Society of Applied Science), 2025)
This community service program aims to improve the ability of educational staff at Yayasan Lazaris, Surabaya, in writing official letters in accordance with the standards outlined in Ministerial Regulation No. 3 of 2021. The training was conducted in two sessions: theoretical and practical, and included a pre-test and post-test assessment. The results showed a significant improvement in participants' competence in understanding official letter formats and using email for formal correspondence. This program has proven to be applicable, relevant, and impactful in strengthening administrative governance and supporting the implementation of the Tri Dharma of Higher Education.